The effect of unemployment on body weight - Sif Jónsdóttir 1986- (2012)
Abstract INTRODUCTION: A positive relationship between economic status and health has been established although causal pathways and mediators are not fully understood. The results of studies on the relationship between unemployment and body weight show a positive relationship between BMI and unemployment at the individual level, while aggregate unemployment is negatively related to a populations BMI. The aim of this study was to examine the relationship between unemployment and changes in body weight following the Icelandic economic collapse of 2008. METHODS: The analysis relies on a health and lifestyle survey “Heilsa og líðan” carried out by The Public Health Institute of Iceland in the years 2007 and 2009. The sample is a stratified random sample of 9.807 Icelanders between the age of 18 and 79. The net response rate in 2007 was 60.8%. In 2009 the response rate was 69.3% of those who participated in the former wave. Thus, a total of 42.1% of the original sample took part in the survey for both years. A linear regression was used when estimating the relationship between job loss and changes in body weight. Mental health was explored as mediator. In total, three models were estimated. RESULTS: Point estimates indicate that both men and women gain less weight in the event of a job loss. The coefficients of job loss were statistically significant for women in model one otherwise they were not statistically significant in any model. The mediation analysis does not show a relationship between mental health and job loss. DISCUSSION: The relationship between job loss and body weight following the economic crisis was inconsistent with ex ante expectations. The results from all three models were inconsistent with results from other studies where job loss has been found to increase body weight. However, body weight has been shown to be procyclical, and the fact that the data used are gathered during a severe economic downturn, might set these current results apart from others. INNGANGUR: Samband efnahagsástands og ...